Development of a Cushion-Shaped Device to Induce Respiratory Rhythm and Depth for Enhanced Relaxation and Improved Cognition - Ban, Yuki; Karasawa, Hiroyuki; Fukui, Rui; Warisawa, Shin'ichi (Frontiers in Computer Science, 2022)
Workplace stress is a pertinent problem in today's world. Preventing and overcoming stress is critical for a healthy lifestyle because it is linked to various health problems and can lead to poor work performance. Controlling your breathing is one of the most effective ways to promote relaxation. However, regulating one's breathing necessitates some training and is not something that everyone can do easily. As a result, we concentrated on the relaxing effect of breathing and developed a cushion-shaped device that displays the desired respiratory motion. We used the effect of inducing one's respiratory movements by watching others' respiratory movements. When the user hugged the device, it changed the user's respiratory rhythm and depth. We conducted a user study with this device, which revealed that presenting respiratory motion can induce the user's respiratory rhythm and depth without any pre-training. Furthermore, subjective evaluation and ECG data suggested that using this device during task breaks can improve the relaxation effect and thus task performance after the break.